Maize yield as affected by the interaction of fertilizer nitrogen and phosphorus in the Guinea savanna of Nigeria - Tofa, A.; Kamara, A.; Babaji, B.A.; Aliyu, K.T.; Ademulegun, T.; Bebeley, J.F. (Elsevier, 2022)
The soils of the Nigeria savannas are particularly low in nitrogen (N) and phosphorus (P) and negatively affects maize productivity. The main objective of the study was to evaluate the interactive effect of N and P fertilizers on maize growth, grain yield, nitrogen uptake and N use efficiency. Field experiments were conducted during the 2015 and 2016 cropping seasons at Iburu in southern Guinea and Zaria in northern Guinea savanna zones of Nigeria. The treatments consisted of three levels of nitrogen (0, 60, and 120 kg N ha−1) and three levels of phosphorus (0, 13, and 26 kg P ha−1). The experimental design consisted of three replications in a split-plot design, with N as the main plot and P as the subplot. Our results show that the response of maize to N depends on the application of P. Higher yields were obtained with the combined application of 120 kg N ha−1 and 26 kg P ha−1 in both locations. With no P applied, plant N uptake (PNU) was greater at N rate of 120 kg ha−1 at Iburu while in Zaria, it increases with increase in N from 0 to 60 kg ha−1. When P was applied at 13 kg ha−1, the PNU increased by 52 and 66% at Iburu while in Zaria the increases were 51 and 57% each with N application of 60 and 120 kg ha−1, respectively, compared with zero N rate. The values for N recovery efficiency (NRE) and agronomic efficiency (AE) were lower for N rate of 120 than for 60 kg ha−1 irrespective of P application rate at both locations. The N utilization efficiency (NUTE) however was higher at 120 N kg ha−1 under 26 kg P ha−1across locations. It can be concluded from these results that in low fertile soils environments such as the Nigeria savannas, N fertilizer should be applied along with P fertilizer for optimum growth, grain yield and nitrogen use efficiency of maize.